Segmental percutaneous central venous line cultures for diagnosis of catheter-related sepsis. Issue 4 (15th December 2011) - Ponnusamy, Vennila; Venkatesh, Vidheya; Curley, Anna; Musonda, Patrick; Brown, Nicholas; Tremlett, Catherine; Clarke, Paul
Abstract : Objective: Culture of percutaneous central venous line (PCVL) segments may assist the diagnosis of line colonisation and catheter-related sepsis (CRS). The authors aimed to determine if the diagnosis of CRS and colonisation of PCVLs in neonates is improved by the culture of the proximal and middle segments of the line in addition to the tip. Patients and methods: In a prospective study, proximal, middle and tip segments of PCVLs indwelling for more than 24 h in term and preterm infants were sent for culture at line removal. Definite CRS was considered as a positive peripheral blood culture plus any line segment growing the same organism in an infant with clinical signs of sepsis. Results: 189 lines were removed from 143 neonates: 142 (75%) were from well infants and 47 (25%) were from neonates with suspected clinical sepsis. The overall CRS rate was 7.9% (15 of 189 line episodes). In well infants, bacterial colonisation rates were significantly higher for proximal segments than for tips (p=0.004). Comparative rates of segmental culture positivity and their positive predictive values for definite CRS were similar for all segments. The diagnosis of CRS was not improved beyond a sole line tip culture by additional middle or proximal segmental cultures or by combinations of the three segments. Conclusion: In well infants, the proximal segments of PCVLs were more often colonised than line tips, but in clinically septic infants preferential culture of proximal or middle segments or combinations of the three segments did not permit better prediction of definite CRS than the culture of the line tip alone. Further studies prior to antibiotic therapy are indicated in babies with suspected CRS.